Delphi definition of the EADC‐ADNI Harmonized Protocol for hippocampal segmentation on magnetic resonance. Issue 2 (14th August 2014) - Boccardi, Marina; Bocchetta, Martina; Apostolova, Liana G.; Barnes, Josephine; Bartzokis, George; Corbetta, Gabriele; DeCarli, Charles; deToledo‐Morrell, Leyla; Firbank, Michael; Ganzola, Rossana; Gerritsen, Lotte; Henneman, Wouter; et al.
Abstract: Background: This study aimed to have international experts converge on a harmonized definition of whole hippocampus boundaries and segmentation procedures, to define standard operating procedures for magnetic resonance (MR)‐based manual hippocampal segmentation. Methods: The panel received a questionnaire regarding whole hippocampus boundaries and segmentation procedures. Quantitative information was supplied to allow evidence‐based answers. A recursive and anonymous Delphi procedure was used to achieve convergence. Significance of agreement among panelists was assessed by exact probability on Fisher's and binomial tests. Results: Agreement was significant on the inclusion of alveus/fimbria ( P  = .021), whole hippocampal tail ( P  = .013), medial border of the body according to visible morphology ( P  = .0006), and on this combined set of features ( P  = .001). This definition captures 100% of hippocampal tissue, 100% of Alzheimer's disease‐related atrophy, and demonstrated good reliability on preliminary intrarater (0.98) and inter‐rater (0.94) estimates. Discussion: Consensus was achieved among international experts with respect to hippocampal segmentation using MR resulting in a harmonized segmentation protocol.